ANTIHYPERTENSIVE THERAPY IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE: ADVANTAGES OF CALCIUM ANTAGONISTS - T. V. Adasheva; I. V. Fedorova; V. S. Zadionchenko; M. V. Macievich; V. V. Lee; S. V. Pavlov (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study effect of antihypertensive therapy with amlodipine maleat (Stamlo® M, “Dr. Reddy’s”, India) on morphofunctional heart indices, intensity of systemic inflammation and oxidative stress in patients with arterial hypertension (HT) with chronic obstructive pulmonary disease (COPD).Material and methods. 20 patients with COPD II-III stage (GOLD 2006) in remission and HT 1-2 stage were involved in the study. Morphofunctional heart indices, respiratory function, levels of C-reactive protein (CRP) and oxidative stress (lipid peroxidation products (LPP) – acilhydroperoxides) were evaluated.Results. Amlodipine maleat therapy provides target level of blood pressure (BP) according to ambulatory BP monitoring with improvement of pathological type of daily BP profile. Reduction of diastolic dysfunction of left and right ventricles was revealed. Therapy was safe in terms of respiratory function. Significant CRP and LPP levels reduction was observed.Conclusion. Amlodipine maleat therapy has high antihypertensive effect, organoprotective properties and safety in hypertensive patients with COPD. Besides this therapy demonstrates systemic anti-inflammatory action and reduces oxidative stress.